Life cycle cost and benefit analysis of low carbon vehicle technologies - Lopez, Neil Stephen A. (Animo Repository, 2018)
The transportation sector is currently responsible for about a quarter of global energy demand and emissions. To limit temperature increase to two degrees Celsius, the International Energy Agency projects that about 21% of emissions reduction should come from transport. In recent years, various alternative technology vehicles have emerged, in response to climate targets. Unfortunately, the sustainable energy wave has made it easy for marketing campaigns to influence and shortcut decision making for deployment of new technologies in some countries. This chapter discusses a life cycle-based cost-benefit analysis framework to serve as decision-support for policy makers in lieu of emerging alternative vehicle technologies. The proposed tool evaluates based on two main impacts: net ownership costs and net external benefits. Within each are more specific cost- and emission-related impacts which are assessed using the AFLEET and GREET tools of the Argonne National Laboratory, and using inputs from published studies. The tool is used to evaluate the effects of shifting to alternative energy vehicle technologies for new and in-use vehicles. The approach is demonstrated via a case study in the Philippines. Results favor LPG as a replacement for in-use, gasoline-powered passenger cars, diesel for new passenger cars, and diesel hybrid electric for public utility jeepneys. The data also reflects the good health and social benefits of electric vehicles, but high fueling infrastructure investment costs deter its deployment. © Springer Nature Singapore Pte Ltd. 2018.